The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2001
DOI: 10.1164/ajrccm.164.11.2101086
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Frequencies and Patterns of Single-nucleotide Polymorphisms in Candidate Genes for Asthma and Atopy in Iceland

Abstract: Numerous asthma and atopy loci have been reported in studies demonstrating associations of the asthma-related phenotypes atopy, elevated IgE levels, and bronchial hyperresponsiveness with alleles of microsatellite markers and single-nucleotide polymorphisms (SNPs) within specific cytokine/chemokine and IgE-regulating genes. Although the studies reporting these observations are compelling, most of them lack statistical power. We assessed the nature, pattern, and frequency of SNPs in 24 candidate genes in Icelan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 68 publications
2
51
1
Order By: Relevance
“…For example, the TT genotype has been associated with an increased risk of asthma in some studies (13,17,20) but not in others (21,32). We found that the CC and CT genotypes of SNP rs1800469 (which were correlated with relatively reduced circulating levels of TGF-b1 in two of three previous studies [ Table 1]) were associated with increased airway responsiveness.…”
Section: Discussionmentioning
confidence: 46%
“…For example, the TT genotype has been associated with an increased risk of asthma in some studies (13,17,20) but not in others (21,32). We found that the CC and CT genotypes of SNP rs1800469 (which were correlated with relatively reduced circulating levels of TGF-b1 in two of three previous studies [ Table 1]) were associated with increased airway responsiveness.…”
Section: Discussionmentioning
confidence: 46%
“…In 2000, Fryer et al [11] first reported the positive association of a single-nucleotide polymorphism [SNP; 342A→G (Ile105Val); rs1695] of GSTP1 with bronchial hyperresponsiveness, skin pick test and asthma. Subsequently, a positive association of this SNP with asthma was reported in Turkish [12, 13] and Taiwanese [14, 15] populations, and a negative association was reported in Icelandic [16] and Russian [17] populations. An association of this SNP with disease susceptibility and gene environmental interaction were also reported in childhood [15, 18] and occupational asthma [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in 2001, deCODE genetics (Reykjavik, Iceland) published the finding that 42 SNPs within 24 ''asthma genes'' did not differ between cases and controls (3). Because only 94 cases and controls were studied, they could only conclude that those mutations were unlikely to incur odds ratios (ORs) greater than 2.…”
mentioning
confidence: 99%